Sexual Function and Quality of Life in a Cohort of Brazilian Users of Two Kind of Intrauterine Contraceptives - Ferreira, Jéssica Mayra; Carreiro, Andréa Vieira; Fernandes, Arlete; Bahamondes, Luis (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To compare sexual function and quality of life (QOL) among intrauterine contraceptive (copper-intrauterine device [Cu-IUD] or the 52-mg 20 µg/day levonorgestrel-releasing intrauterine system [LNG-IUS]) users.Methods This was part of a cross-sectional study. Women aged between 18 and 49 years old, in a heterosexual relationship, reporting sexual intercourse in the previous 4 weeks, using Cu-IUD (Group 1) or LNG-IUS (Group 2) responded to a questionnaire with sociodemographic information, to the Female Sexual Function Index (FSFI), to the World Health Organization QOL Questionnaire Abbreviated Version (WHOQOL-BREF), and to a questionnaire about the contraceptive method used. The Student t-test, the Pearson χ2 test or the Fisher exact test, and the Mann-Whitney test were used for the analysis. For the adjusted comparison, we have used the analysis of covariance (ANCOVA). A multiple regression analyzing factors related to FSFI ≤ 26.55 was done. Significance was established at p < 0.05.Results A total of 347 women in Group 1 (mean age of 32.3 ± 7.5 years old) and of 298 in Group 2 (mean age of 32.7 ± 6.4 years old) completed the questionnaires. Most women had ≥ 8 years of schooling, were in a monogamous relationship, and had had ≤ 2 pregnancies. A total of 122 Cu-IUD and of 87 LNG-IUS users scored ≤ 26.55 on the FSFI. Significant lower scores in physical, environmental, and overall QOL domains in the WHOQOL-BREF questionnaire were found in Group 1. More women using the Cu-IUD were not satisfied with the method.Conclusion We did not find significant differences in sexual function; there was a lower score in some domains of QOL among women who used the Cu-IUD. It was not possible to ensure that those differences were related to the contraceptive method.
Keywords: contraception; quality of life; sexuality